Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0034827
|View full text |Cite
|
Sign up to set email alerts
|

Musashi2 Is Required for the Self-Renewal and Pluripotency of Embryonic Stem Cells

Abstract: Recent studies have shown that the RNA binding protein Musashi 2 (Msi2) plays important roles during development. Msi2 has also been shown to be elevated in several leukemias and its elevated expression has been linked with poorer prognosis in these cancers. Additionally, in embryonic stem cells (ESC) undergoing the early stages of differentiation, Msi2 has been shown to associate with the transcription factor Sox2, which is required for the self-renewal of ESC. These findings led us to examine the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…S4, supplemental Table S6). Recently, we have shown that Msi2 is required for the self-renewal and pluripotency of mouse ESC [14] and, more recently, we have determined that knockdown of Usp9x in mouse ESC substantially increases the differentiation of ESC (unpublished results). Furthermore, MSI2 and USP9X have been implicated in other cancers [16][21], but their roles in brain tumors have not been examined.…”
Section: Resultsmentioning
confidence: 83%
“…S4, supplemental Table S6). Recently, we have shown that Msi2 is required for the self-renewal and pluripotency of mouse ESC [14] and, more recently, we have determined that knockdown of Usp9x in mouse ESC substantially increases the differentiation of ESC (unpublished results). Furthermore, MSI2 and USP9X have been implicated in other cancers [16][21], but their roles in brain tumors have not been examined.…”
Section: Resultsmentioning
confidence: 83%
“…In addition, Msi2 isoform 2 appears to be the major isoform expressed in bladder cancer cell lines and tissues, which was consistent with the expression pattern of Msi2 in glioblastoma cells and embryonic stem cells. 18,19 Clinical analysis also indicated that high expression of Msi2 was correlated with poor overall and Msi2 promotes bladder cancer metastasis via JAK2/STAT3 pathway C Yang et al recurrence-free survival in patients with bladder cancer. Moreover, in vitro assays indicated that overexpression of Msi2 promoted, while silencing of Msi2 inhibited, the migration and invasiveness of bladder cancer cell through activating JAK2/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Separate lentiviral vectors were generated with pLVX-tetO-(fs)SOX2 and with a vector expressing the reverse tet transactivator, pLVX-Tet-On® Advanced (modified to use a PGK rather than a CMV promoter) [66]. Cells which successfully integrated these viral vectors were selected for in medium containing 5 μg/ml puromycin (P8833, Sigma-Aldrich, St. Louis, MO) for 48 hours and 300 μg/mL G418 sulfate (#631308, Clontech, Mountain View, CA) for 9-12 days, respectively.…”
Section: Methodsmentioning
confidence: 99%